Analysis of cardiopulmonary and metabolic variables measured during laboratory and sport-specific incremental tests for table tennis performance prediction - Zagatto, Alessandro Moura [UNESP]; Papoti, M.; Reis, I. G. M. dos; Beck, W. R.; Gobatto, C. A. (Elsevier B.V., 2014)
Purpose. - The purposes of this study were: i) to compare the physiological responses measured during a specific table tennis incremental test with the physiological responses measured during cycling, arm cranking, and treadmill running tests; and ii) to verify the accuracy of table tennis performance prediction based on the physiological responses from these tests.Methods. - Eleven national level male table tennis players participated in the study and undertook incremental tests using ergometers. Table tennis performance was defined as the ranking obtained during a simulated tournament between the participants.Results. - In general, peak values for physiological variables (e.g., (V) over dotO(2PEAK) and [La]PEAK) were significantly lower (P < 0.05) in the specific test (e.g., (V) over dotO(2PEAK) = 39.9 +/- 1.5 ml.kg(-1) per minute and [La]PEAK = 6.4 +/- 0.5 mmol.L-1) than during cycling (e.g., (V) over dotO(2PEAK) = 41.3 +/- 1.4 ml.kg(-1) per minute and [La]PEAK = 10.2 +/- 0.7 mmol.L-1) or running (e.g., (V) over dotO(2PEAK) = 43.9 +/- 1.5 ml.kg(-1) per minute and [La]PEAK = 10.0 +/- 0.7 mmol.L-1), but higher than during arm cranking (e.g., (V) over dotO(2PEAK) = 26.6 +/- 1.6 ml.kg(-1) per minute and [La]PEAK = 8.9 +/- 0.6 mmol.L-1). At respiratory compensation point intensity (RCP), only the variables measured on arm cranking were lower (P < 0.05) than on the other ergometers. Stepwise multiple regression analysis showed significant correlation between table tennis performance and lactate concentration ([La]) and also rate of perceived effort (RPE) at RCP during cycling (r = 0.89; P < 0.05).Conclusion. - In conclusion, the significant differences obtained between the specific and laboratory ergometers demonstrate the need to use a specific test to measure physiological parameters in table tennis and the physiological parameters measured, independent of the ergometer used, are unable to predict table tennis performance. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Peak oxygen uptake; Blood lactate; Respiratory compensation point; Specificity; Gas exchange